Identificación de la dinámica del crecimiento de vegetación a nivel macro en la frontera páramobosque de la hacienda Yanahurco - González Soto, Fernando Alexis (2018)
Abstract:In Ecuador there is a constant deterioration of paramo and forest ecosystems due to environmental and human pressures. In the environmental aspect, these ecosystems that develop especially at altitudes higher than 2.800 m s.n.m. They are sensitive to changes in weather patterns, however, little has been studied on how much the growth of plant species in that area has been affected. In this study, the dynamics of vegetation growth in these ecosystems (paramo, forest), were determined from an analysis of Mann Kendall in a 17-year data series and a creation of zonas of the growth slope variables that could be influencing that dynamic (slope, distance, vegetation type, altitude). Among the main results, the growth dynamics was higher in the border area and in forest areas near watercourses. Key words: vegetation growth dynamics, GIS, EVI, Mann Kendall, climate change, paramo-forest border.